Differential expression of microRNAs and tRNA fragments mediate the adaptation of the liver fluke Fasciola gigantica to its intermediate snail and definitive mammalian hosts. Issue 5 (April 2021) - Hu, Rui-Si; Zhang, Xiao-Xuan; Ma, Qiao-Ni; Elsheikha, Hany M.; Ehsan, Muhammad; Zhao, Quan; Fromm, Bastian; Zhu, Xing-Quan
Graphical abstract: Highlights: Fifty-six microRNAs (miRNAs) from 33 conserved families and four Fasciola -specific miRNAs were identified. miRNAs are mainly involved in the regulation of metabolism, biosynthesis, growth and developmental processes. The expression profiles of 5′ halves derived by tRNA -Lys and tRNA -Gly were mainly related to the buffalo-infecting stages. This study provided an overview of the dynamic changes of small RNAs that occur during the lifecycle stages of F. gigantica. This global analysis of F. gigantica lifecycle stages revealed new roles of miRNAs and tRFs in parasite development. Abstract: The tropical liver fluke Fasciola gigantica affects livestock and humans in many Asian countries, large parts of Africa, and parts of Europe. Despite the public health and economic impacts of F. gigantica, understanding of F. gigantica biology and how the complex lifecycle of this liver fluke is transcriptionally regulated remain unknown. Here, we tested the hypothesis that the regulatory small non-coding RNAs (sncRNAs), microRNAs (miRNAs) and tRNA-derived fragments (tRFs) play roles in the adaptation of F. gigantica to its intermediate and definitive hosts. We sequenced sncRNAs of eight lifecycle stages of F. gigantica . In total, 56 miRNAs from 33 conserved families and four Fasciola -specific miRNAs were identified. Expression analysis of miRNAs suggested clear stage-related patterns. By leveraging the existing transcriptomic data, we predicted a miRNA-based regulation of metabolism, transport, growth and developmental processes. Also, by comparing miRNA complement of F. gigantica with that of Fasciola hepatica, we detected a high level of conservation and identified differences in some miRNAs, which can be used to distinguish the two species. Moreover, we found that tRFs at each lifecycle stage were predominantly derived by tRNA -Lys and tRNA -Gly at 5′ half sites, but relatively high expression was related to the buffalo-infecting stages. Taken together, we provided a comprehensive overview of the dynamic transcriptional changes of small RNAs that occur during the developmental stages of F. gigantica . This global analysis of F. gigantica lifecycle stages revealed new roles of miRNAs and tRFs in parasite development and will facilitate future research into understanding of fasciolosis pathobiology.